Diversity of Fireflies (Coleoptera: Lampyridae) In the Manguang Pariaman Mangrove Forest - sonya falenia; rijal satria (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Fireflies are a type of insect that has the ability to emit light, especially at night or in dark conditions. This study aims to determine the diversity of fireflies species in the Mangrove Mangguang Pariaman forest in 2019-2020. The method used is a survey method, namely by catching fireflies with insect nets in several locations. The results showed that one firefly species was found in the Mangguang Mangrove Forest which belonged to the subfamily Luciolinae, genus Pteroptyx and species Pteroptyx tener. Pteroptyx tener was found in three mangrove species, namely Sonneratia, Rhizophora, and Acanthus. Pteroptyx tener was most commonly found in the Sonneratia mangroves with fifteen males and five females. In Rhizophora mangroves, ten males and four females were found. While in the Acanthus mangrove there are seven male individuals and three female individuals. The total individuals found from the Pteroptyx tener species were forty-three individuals.